Review of bioindicator species in environmental assessment (Zoological Records and Reviews, 2025)
Bioindicator species -- organisms whose presence, abundance, condition, or behaviour reflects the ecological integrity ofthe environment they inhabit -- have been a cornerstone of environmental monitoring since Kolkwitz and Marsson'ssaprobic system of 1908, yet the rigour with which candidate bioindicators are validated, applied, and reported remainshighly variable across taxonomic groups, environmental media, and regulatory frameworks. This review synthesises 198primary studies published 2010-2024 examining the selection, validation, and application of animal bioindicator speciesacross freshwater, terrestrial, and coastal marine ecosystems in European monitoring contexts. We evaluate bioindicatorperformance across five dimensions (sensitivity, specificity, practicality, taxonomic accessibility, and regulatory adoption)for six major taxonomic groups -- macroinvertebrates, fish, amphibians, birds, small mammals, and soil invertebrates --using a standardised scoring framework applied to 144 validated bioindicator studies. Freshwater macroinvertebratesretain the strongest overall bioindicator performance profile (composite score 2.64/3.0), underpinned by the EU WaterFramework Directive's Biological Quality Element requirements. Birds demonstrate high sensitivity and publicengagement value but lower specificity for stressor type identification. Amphibians -- particularly Rana and Triturus spp.-- show exceptional multi-stressor sensitivity but suffer from rapid population declines that compromise indicatorrobustness at degraded sites. Emerging approaches -- environmental DNA (eDNA) metabarcoding, passive acousticmonitoring, and wearable biologger-based behavioural biomarkers -- are evaluated as next-generation bioindicatorplatforms. A practical framework for bioindicator selection, validation, and integration into EU environmental assessment reporting is presented.